Transferrin and antioxidants partly prevented mouse oocyte oxidative damage induced by exposure of cumulus-oocyte complexes to endometrioma fluid - Zi Ren; Jiana Huang; Chuanchuan Zhou; Lei Jia; Manchao Li; Xiaoyan Liang; Haitao Zeng (BMC, 2020)
Abstract Background Exposure of oocytes to the endometrioma fluid has an adverse effect on embryonic quality. To determine whether adding transferrin and antioxidants to culture medium could counteract detrimental effects on mouse cumulus-oocyte complexes (COCs) induced by exposure to endometrioma fluid or not, we conducted an in vitro cross-sectional study using human and mouse COCs. Methods Eighteen women who had their oocytes exposed to endometrioma fluid during oocyte retrieval were enrolled. COCs from superovulated ICR female mice were collected. They were first exposed to human endometrioma fluid and then treated by transferrin and/or antioxidants (cysteamine + cystine). Subsequently, COCs function was assessed by molecular methods. Results This study observed that human COCs inadvertently exposed to endometrioma fluid in the in vitro fertilization (IVF) group led to a lower good quality embryo rate compared to intracytoplasmic sperm injection (ICSI) group. Exposure of mouse COCs to endometrioma fluid accelerated oocyte oxidative damage, evidenced by significantly reduced CCs viability, defective mitochondrial function, decreased GSH content and increased ROS level, associated with the significantly higher pro-portion of abnormal spindles and lower blastocyst formation (p < 0.05, respectively). This damage could be recovered partly by treating COCs with transferrin and antioxidants (cysteamine + cystine). Conclusions Transferrin and antioxidants could reduce the oxidative damage caused by COCs exposure to endometrioma fluid. This finding provides a promising new possibility for intervention in the human oocyte oxidative damage process induced by endometrioma fluid during oocyte pick-up.